Distance Characteristics of Sound Wave Attenuation in ER Fluids - Nanhui Yu; Jijun Fan (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Electrorheological fluids(ER fluid) as an electrically controllable acoustic medium has been proved by experimental studies. In this paper,the sound attenuation in ER fluid at different propagation distances was experimentally studied. The results show that sound attenuation of ER fluid could be adjusted by the particle concentration of ER fluid and the intensity of electric field. Amplitude of sound wave in ER fluid increases with the increasing of particle concentration and field intensity; on the other hand, the attenuation of sound wave decreases with the increasing of propagation distance, as well as the particle concentration and field intensity. The experimental results indicate that the solidification effect of ER fluid is beneficial to the propagation of sound wave. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1994